2017
DOI: 10.1007/s00265-017-2332-2
|View full text |Cite|
|
Sign up to set email alerts
|

Differences in social preference between the sexes during ontogeny drive segregation in a precocial species

Abstract: Hypotheses for why animals sexually segregate typically rely on adult traits, such as differences in sexual roles causing differential habitat preferences, or size dimorphism inducing differences in diet or behaviour. However, segregation can occur in juveniles before such roles or size dimorphism is well established. In young humans, leading hypotheses suggest that (1) sexes differ in their activity and the synchronisation of behaviour causes segregation and (2) sexes separate in order to learn and maximise f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 71 publications
3
19
1
Order By: Relevance
“…Our results show that soon after hatching (Experiment 1) chicks discriminate between sexes and preferentially approach female peers. This spontaneous preference is partially in line with the observations of Whiteside et al (2017), who found that in the first week, female pheasants chicks preferred to associate with their own sex peers, while male pheasant chicks exhibited a random assortment. At hatching, chicks appear sexually monomorphic, and in line with this we did not find significant differences in the weight of males and females.…”
Section: Discussionsupporting
confidence: 88%
“…Our results show that soon after hatching (Experiment 1) chicks discriminate between sexes and preferentially approach female peers. This spontaneous preference is partially in line with the observations of Whiteside et al (2017), who found that in the first week, female pheasants chicks preferred to associate with their own sex peers, while male pheasant chicks exhibited a random assortment. At hatching, chicks appear sexually monomorphic, and in line with this we did not find significant differences in the weight of males and females.…”
Section: Discussionsupporting
confidence: 88%
“…However, we did not observe differences in crop content when considering a suite of common food items. Similarity in dietary preference was also observed in pheasants when tested as chicks in captivity and presented with a choice of a variety of natural and man-made food items ( Whiteside et al, 2017 ). Dietary difference between sexes often occurs, or become more pronounced, in periods leading up to nesting and incubation ( Lewis et al, 2002 ; Nisbet, 1997 ).…”
Section: Discussionmentioning
confidence: 56%
“…Such segregation persists until early March ( Hill & Ridley, 1987 ; Hill & Robertson, 1988 ) when harems of females visit and eventually join territory-holding males, which likely reduces their harassment by other males ( Ridley & Hill, 1987 ) and allows females to decrease their vigilance levels and so increase time spent foraging ( Whiteside, Langley & Madden, 2016 ), until they independently start to nest and incubate their eggs ( Taber, 1949 ). Pheasants become sexually dimorphic by three weeks of age ( Whiteside et al, 2017 ), and chicks in captivity (<8 weeks old) exhibit preference for their own sex ( Whiteside et al, 2017 ). As adults, males have highly conspicuous plumage and are 40% larger than the cryptic females ( Wittzell, 1991 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations